2015
DOI: 10.2105/ajph.2014.302176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particulate Matter and Antioxidant Dietary Intake on Blood Pressure

Abstract: Objectives We assessed 2 pathways through which dietary antioxidants may counter adverse effects of exposure to particulate matter less than 2.5 micrometers in diameter (PM2.5) on blood pressure (BP): main (compensatory) and modifying (protective) models. Methods We used 2002 to 2003 data from the Detroit Healthy Environments Partnership community survey conducted with a multiethnic sample of adults (n = 347) in low- to moderate-income, predominantly Hispanic and non-Hispanic Black neighborhoods in Detroit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 68 publications
8
19
1
Order By: Relevance
“…29, 30 One study from Detroit also reported that antioxidant intake may protect against cardiovascular effects of PM 2.5 . 31 Taken together, our study supported an intervention through increasing intake of fruit and vegetables to reduce the adverse effects of ambient PM 2.5 exposure.…”
Section: Discussionsupporting
confidence: 66%
“…29, 30 One study from Detroit also reported that antioxidant intake may protect against cardiovascular effects of PM 2.5 . 31 Taken together, our study supported an intervention through increasing intake of fruit and vegetables to reduce the adverse effects of ambient PM 2.5 exposure.…”
Section: Discussionsupporting
confidence: 66%
“…Results obtained in the current study generally provide evidence in support of the hypothesis that intake of micronutrients-rich diets may modify the adverse effects of PM 2.5 on BP as reported by Schulz et al (2015). For instance, in the joint effect model ( Supplementary Table 4), adequate Fe intake dampened the effects of exposure to higher levels of PM 2.5 on SBP after controlling for covariates in e-waste recyclers.…”
Section: Effects Of Dietary Micronutrient Intake On the Association Bsupporting
confidence: 86%
“…Several studies have reported the adverse effects of PM 2.5 on BP outcomes(Majkova et al, 2010;Nachvak et al, 2016;Schulz et al, 2015; Whyand et al, 2018), with few focusing on how intake of micronutrient-rich diets may ameliorate these effects. To the best of our knowledge, this study is the first-ever to examine the role of micronutrient-rich dietary intake in reducing the harmful effects of PM among e-waste recyclers.…”
mentioning
confidence: 99%
“…One study from Detroit also reported that dietary antioxidant intake may protect against the adverse cardiovascular effects of ambient PM 2.5 . 41 A cohort study in Mexico reported that a high intake of fruit could modulate the adverse effect of O 3 on lung function among children. 42 Studies from Spain and Denmark also suggested that intake of fruit was associated with decreased mental health effects of air pollution.…”
Section: Discussionmentioning
confidence: 99%